Pengenalan Digital Marketing di Era Media Sosial bagi Siswa SMA Carnegie Medan - Sjukun Sjukun; Fenny Fenny; Wily Julitawaty; Widalicin Januarty; Yusuf Taufik (CV. Armas Suan Sejahtera, 2025)
This community service activity aims to provide basic digital marketing education to students of Carnegie Senior High School Medan, with a particular focus on the utilization of social media as a modern and relevant marketing tool in the digital era. The background of this activity is based on the high intensity of social media usage among adolescents, which is not always accompanied by sufficient understanding of its productive and ethical use. Therefore, early education is needed to introduce students to the positive and strategic potential of digital platforms.The implementation methods included the delivery of learning materials in an interactive manner, group discussions, and simple case studies that were closely related to students’ daily experiences. The materials covered fundamental concepts of digital marketing, types of social media platforms used for marketing purposes, digital-based business opportunities, and the importance of ethics and responsibility in digital activities.The results of the activity indicate a significant improvement in students’ understanding of basic digital marketing concepts and a shift in perception regarding social media, from being merely a means of entertainment to a platform with economic value. In addition, students demonstrated increased awareness of ethical behavior in online interactions and transactions. They also showed strong enthusiasm during discussions and were able to identify simple business ideas that could be developed through digital platforms. This activity serves as a strategic initial step in instilling digital entrepreneurship awareness at the secondary education level and contributes to preparing young generations who are adaptive, creative, and responsible in facing the challenges of the digital economy.